Circus Caps for Sale - Slobodkina, Esphyr; 1908-; Slobodkina, Esphyr; Slobodkina, Esphyr ([New York], 2002)
A peddler who sells caps by balancing them all on his head is invited to do an act in the circus.
"A companion to Caps for sale"--Cover.
"Originally published as Pezzo the peddler and the circus elephant by Abelard-Schuman, 1967"--P. facing the t.p.
Keywords: Hats; Fiction; Peddlers and peddling; Fiction; Circus; Fiction